2014
DOI: 10.1061/(asce)cc.1943-5614.0000441
|View full text |Cite
|
Sign up to set email alerts
|

URM Walls Strengthened with Fabric-Reinforced Cementitious Matrix Composite Subjected to Diagonal Compression

Abstract: Unreinforced masonry (URM) walls have been constructed for the past millennia and are still widely used today. URM walls have proven to have low shear strength and are prone to brittle failure when subjected to in-plane loads caused by earthquake or wind. Retrofitting URM walls is accomplished internally and externally using current techniques, such as placing steel bars in the cavities and grouting, posttensioning with steel tendons, stitching, and adhering fiber-reinforced polymers (FRP) to increase capacity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
61
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(65 citation statements)
references
References 13 publications
2
61
0
2
Order By: Relevance
“…The shear modulus, G, was calculated as G= cr / cr , where cr is the diagonal cracking strength and cr is the corresponding shear strain. The diagonal cracking strength was defined as cr = max , for the control (unretrofitted) specimens and as cr =0.7 max , for the retrofitted ones, consistent with a number of studies, including the recent ones of Dizhur et al (2013), Parisi et al (2013) and Babaeidarabad et al (2014).…”
Section: Diagonal Compression Tests On Masonry Wallettesmentioning
confidence: 99%
See 1 more Smart Citation
“…The shear modulus, G, was calculated as G= cr / cr , where cr is the diagonal cracking strength and cr is the corresponding shear strain. The diagonal cracking strength was defined as cr = max , for the control (unretrofitted) specimens and as cr =0.7 max , for the retrofitted ones, consistent with a number of studies, including the recent ones of Dizhur et al (2013), Parisi et al (2013) and Babaeidarabad et al (2014).…”
Section: Diagonal Compression Tests On Masonry Wallettesmentioning
confidence: 99%
“…The use of textile-reinforced mortar (TRM) as strengthening material for substandard reinforced concrete (RC) members , Bournas et al 2007, Bournas et al 2009, Al-Salloum et al 2011) and for masonry panels , Papanicolaou et al 2008, Harajli et al 2010, Parisi et al 2013, Babaeidarabad et al 2014) has been experimentally investigated in the past and has been reported to be effective in the majority of the cases. In the recent past the authors presented a concept for strengthening masonry-infilled RC frames with TRM.…”
Section: Introductionmentioning
confidence: 99%
“…cement-based mortars) for strengthening reinforced concrete structures has been reported less than a decade ago by , and Bournas et al (2007); and more recently by D'Ambrisi and Focacci (2011), Al-Salloum et al (2011, 2012 and Loreto et al (2014). Tests on masonry sub-assemblies and wallettes have provided experimental evidence that TRM is effective in strengthening masonry structures too, as it enhances both the in-plane and out-of-plane strength , Papanicolaou et al 2008, Harajli et al 2010, Augenti et al 2011, Papanicolaou et al 2011, Babaeidarabad et al 2013, as well as the strength in diagonal compression (Prota et al 2006, Babaeidarabad et al 2014. Nonetheless, in all these studies individual, single storey wall-type masonry specimens were employed, without considering the frame-wall interaction in multistorey structures.…”
Section: Introductionmentioning
confidence: 99%
“…The use of FRP (Fiber Reinforced Polymers) materials are particularly suited to strengthening pre-existing masonry constructions and can be used to extend the fatigue life or provide an increase in strength of a structure [1][2][3][4].…”
Section: Introduction and Research Significancementioning
confidence: 99%